Pengaruh Risiko dan Harga terhadap Keputusan Pembelian melalui Kepercayaan Konsumen - -, Murwatiningsih; Apriliani, Erin Puri (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2013)
This research aims at knowing the direct and indirect influence of risk and price to online purchasing decision through trust, and the influence of trust to online purchasing decision. The population of this research is 291 consumers. Slovin formula is used for obtaining 74 respondents as the sample. Questionnaire and documentation are the methods for collecting the data. In analyzing the data, path analysis is applied. The results of this research show that risk influences online purchasing decision, but price does not influence online purchasing decision. Then, trust influences online purchasing decision; and it mediates the influence of risk and price to online purchasing decision. The conclusion of this research is that the higher of consumers trust will increase the online purchasing decision although it may make higher risk and higher price for consumers